2022
DOI: 10.3389/fpsyt.2022.897806
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Trajectories of Hikikomori Symptoms During Job Search and the Role of Identity Distress: Three Wave Longitudinal Research

Abstract: ObjectiveHikikomori, a prolonged form of social withdrawal, has received attention in various research areas. This longitudinal study aimed to identify diverse trajectories of hikikomori symptoms among young Japanese adults engaged in a job search. It also tested whether identity distress, a critical developmental issue, predicts these trajectories while controlling for other risk factors (depressive symptoms, life satisfaction, career expectations, and gender).MethodsA total of 756 third-year Japanese univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These studies show that withdrawal symptoms in most young people are at a stable low level (i.e., reflecting the normative development), but that there also are subgroups of youth (a) showing stable high levels of withdrawal symptoms or (b) who gradually develop such symptoms over time or-in contrast-(c) who initially display clear withdrawal symptoms but gradually become more socially involved. In addition to this, a recent longitudinal study by Hihara et al (2022) indicated that once symptoms of ESW are in the severe range, they tend to escalate over time.…”
Section: A Developmental Psychopathology Framework For Eswmentioning
confidence: 97%
“…These studies show that withdrawal symptoms in most young people are at a stable low level (i.e., reflecting the normative development), but that there also are subgroups of youth (a) showing stable high levels of withdrawal symptoms or (b) who gradually develop such symptoms over time or-in contrast-(c) who initially display clear withdrawal symptoms but gradually become more socially involved. In addition to this, a recent longitudinal study by Hihara et al (2022) indicated that once symptoms of ESW are in the severe range, they tend to escalate over time.…”
Section: A Developmental Psychopathology Framework For Eswmentioning
confidence: 97%
“…In turn, social isolation, financial strain, and loneliness have been associated with suicidal ideation (Elbogen et al, 2021). Hihara et al (2022) recently found that most of the 756 Japanese university graduates displayed severe social withdrawal symptoms during job search and this was linked to higher identity distress.…”
Section: Introductionmentioning
confidence: 99%